Implementasi Asas Keseimbangan dalam Perjanjian Hubungan Kemitraan Transportasi Online di Indonesia - Ulil Alba, S.H.S; Mbunai, La Ode; Bahari, Syaiful; Suparman, Yusup (JUSTLAW : Journal Science and Theory of law, 2025)
The development of digital technology has driven significant changes in the transportation sector through the presence of app-based transportation services in Indonesia. The relationship between online transportation companies and drivers is built in the form of a partnership, but in practice it raises legal issues, particularly regarding the certainty of the driver's legal status and the application of the principle of balance in partnership agreements. This study aims to analyze online transportation partnership relationships in Indonesia and examine the application of the principle of contractual balance in these relationships. The research method used is normative legal research with a statutory approach and a conceptual approach, through a review of relevant laws and regulations, doctrines, and legal literature. The results show that online transportation partnership relationships have not received clear regulations in the labor law regime, thus creating a legal vacuum. Although the concept of partnership normatively requires equal standing between the parties, practice in the field demonstrates an imbalance between app companies and drivers. This imbalance is reflected in the use of unilaterally drafted standard agreements, the existence of exoneration clauses, work control through algorithmic systems, and limited driver access to data and information. These conditions result in the principles of balance and proportionality in partnership agreements not being optimally met and potentially detrimental to drivers. Therefore, this study emphasizes the need for more comprehensive and adaptive legal regulations to ensure a balance of rights and obligations and provide fair legal protection for online transportation drivers in Indonesia.